A new approach of image inpainting in the wireless environment. (9th September 2013) - Kao, Yang–Ta; Hung, Lun–Ping; Chen, Wei–Ming
The technology of image inpainting has provided an opportunity to remedy damaged films, especially when scenes cannot be reconstructed or having the difficulties to reshoot the same film. Repairing damaged films can enhance the readability of films and provide meaningful information to readers. In the field of medical treatment, medical video films offer a solid support for the clinical treatment. Thus, developing image repairing technology can enhance the quality of medical treatment. In this paper, we introduce a new algorithm of defect detection that can detect spikes and scratch line appearing in damaged films correctly. Also, another new algorithm is proposed to repair these two kinds of defects. Using vivo photography as an example, damaged film transmitted through wireless environment can be detected and repaired. Experimental results on the detection and the restoration of damaged medical video demonstrate the efficiency of our proposed algorithm outperform some well–known image inpainting algorithm.